Better than before [compact disc, unabridged] - Rubin, Gretchen (Random House Audio, 2015)
"Habits are the invisible architecture of our lives. Rubin provides an analytical and scientific framework from which to understand these habits--as well as change them for good. Infused with her compelling voice and funny stories, she illustrates the core principles of habit formation with dozens of strategies that she uses herself and tests out on others. Rubin provides tools to help readers better understand themselves, and presents a clear, practical menu of strategies so readers can take an individualized approach. She tackles each strategy herself and in doing so shows us the importance of knowing ourselves and our own habit tendencies. Armed with self-knowledge, we can pursue habits in ways that will truly work for us, not against us. Going to the gym can be as easy, effortless, and automatic as putting on a seatbelt. We can file expense reports, take time for fun, or pass up that piece of carrot cake without having to decide. With a foundation of good habits, we can build a life that reflects our values and goals"--